2009
DOI: 10.1093/jpepsy/jsp021
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Children's Response to Serious Illness: Perceptions of Benefit and Burden in a Pediatric Cancer Population

Abstract: The BBSC is internally reliable and preliminary data supports the validity of separate benefit and burden constructs. Children report positive and negative aspects of their illness simultaneously, and perceptions of benefit and burden function as independent constructs. The BBSC is a useful measure for pediatric cancer patients that could be applied to children experiencing other significant life events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
84
3
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(103 citation statements)
references
References 18 publications
13
84
3
3
Order By: Relevance
“…Studies could also be improved by using existing theoretical models to develop hypotheses about children's response to genetic information about health. [62][63][64][65][66][67][68][69][70][71][72] Including less extensively studied concepts such as benefit finding, [63][64][65] hoped for and feared possible selves, 66,67 adaptive coping, 63,68 resilience traits, 69 and communal coping responses 70 may lead to a richer understanding of children's testing experienced. Furthermore, research that examines the translational potential of genomic or genetic testing of children (e.g., studies assessing methods for communicating test results, approaches for the use of testing in clinical settings, and influences of testing on health or health behavior outcomes) should be considered alongside psychosocial effects so as to make possible a balanced risk/benefit analysis before the test implementation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies could also be improved by using existing theoretical models to develop hypotheses about children's response to genetic information about health. [62][63][64][65][66][67][68][69][70][71][72] Including less extensively studied concepts such as benefit finding, [63][64][65] hoped for and feared possible selves, 66,67 adaptive coping, 63,68 resilience traits, 69 and communal coping responses 70 may lead to a richer understanding of children's testing experienced. Furthermore, research that examines the translational potential of genomic or genetic testing of children (e.g., studies assessing methods for communicating test results, approaches for the use of testing in clinical settings, and influences of testing on health or health behavior outcomes) should be considered alongside psychosocial effects so as to make possible a balanced risk/benefit analysis before the test implementation.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Phipps and colleagues (2007) reported that BF was unrelated to PTSD, global quality of life and pessimism. Moreover, other studies showed that BF was also unrelated to anxiety (Currier et al, 2009;Helgeson et al, 2006), depressive symptoms (Currier et al, 2009;Vaughn, Roesch, & Aldridge, 2009) and aggressive beliefs . In sum, the relation between BF and measures of psychological distress is still controversial.…”
Section: Introductionmentioning
confidence: 91%
“…Most of these constructs have been broadly studied in adults (for review, see Helgeson et al, 2006), but less so in pediatric research. Although some previous studies included some of these constructs (Currier et al, 2009;Phipps et al, 2007;Hedström, Skolin & von Essen, 2004), their association with BF is still poorly understood.…”
Section: Benefit Finding and Well-being In Children With Life Threatementioning
confidence: 99%
See 2 more Smart Citations